The simultaneous removal of SO2 and NO from flue gas over activated coke in a multi-stage fluidized bed at low temperature. (1st September 2020) - Li, Yunjia; Zhang, Xiaoling; Huangfu, Lin; Yu, Fengqin; Chen, Zhaohui; Li, Changming; Liu, Zhouen; Yu, Jian; Gao, Shiqiu
Abstract: A multi-stage fluidized bed (MSFB) process was explored to simultaneously remove the SO2 and NO x from flue gas by use of activated coke (AC) as active medium in low temperature range of 100–200 °C. The various technological tests (e.g., temperature, feeding rate, superficial gas velocity, bed numbers) were carried out to make clear the removal features of SO2 and NO x in MSFB system. The MSFB process could not only increase both the removal efficiency and capacity of SO2 over AC, but also eliminate SO2 in the first layer of bed to avoid poisoning the AC by ammonium sulphate in upper beds for denitration. 100% desulfurization efficiency and 73.2% denitration efficiency could be acquired over regenerated AC through the four-stage bed at 180 °C in the presence of 10 vol% H2 O, which was even much more efficient than moving bed process. Moreover, the fresh AC could be activated after the use/regeneration circulation of AC, and the removal efficiency for both SO2 and NO was significantly elevated over the regenerated AC. The multiple structural characterizations (BET, FT-IR, TPD, XPS) revealed that the microporous structure of regenerated AC was expanded with increased surface area and pore volume to provide more adsorption sites for SO2, and meanwhile abundant surface nitrogen/sulfur/oxygen groups were produced as catalytic sites for denitration, accounting for the significantly promoted removal efficiency over the regenerated AC. The demonstrated advantages of MSFB system signify its promising application prospect for the simultaneous removal of SO2 and NO x in industry.